The analysis of current approaches towards developing professional mobility of future specialists (Pedagogy of Higher and Secondary Education, 2014)
Tsys O. А. The analysis of current approaches towards developing professional mobility of future specialists.The article reveals different approaches (personality-oriented, system, subject and activity) to form professional mobility of future specialists. The author suggests results of theoretical analysis of scientific and educational literature connected with approaches towards developing professional mobility of future specialists. The areas for further researches are defined.
Keywords: professional mobility; developing professional mobility; system approach; personality-oriented approach; subject and activity approach